Characterisation of Persistent Anti-Xa Activity Following Administration of the Low Molecular Weight Heparin Enoxaparin Sodium (Clexane) - Brieger, David; Dawes, Joan (Thrombosis and Haemostasis, 1994)
It is widely reported that persistent anti-Xa activity follows administration of low molecular weight heparins. To identify the effectors of this activity we have injected 125I-labelled Enoxaparin sodium into rabbits and subsequently analysed the circulating radiolabelled material and anti-Xa activity by affinity and size exclusion chromatography. Antithrombin III-binding material derived from the injected drug was responsible for all the anti-Xa amidolytic activity. At early times after injection additional anticoagulant activity which was largely attributable to tissue factor pathway inhibitor was measured by the Heptest clotting assay after removal of glycosaminoglycans from plasma samples. Small radiolabelled fragments, including penta/hexasaccharide with affinity for antithrombin III, were detectable in the circulation 1 week later, and sulphated oligosaccharides persisted for 3-4 weeks. Significant quantities of radiolabel remained in the liver and kidney several weeks post-injection; these organs may sequester some of the injected drug and give rise to circulating biologically active material by degradation and secretion of catabolic products into the plasma.